VARIASI KOMPOSISI DINDING CANGKANG FOSIL FORAMINIFERA BENTONIK UNTUK PENENTUAN LINGKUNGAN PENGENDAPAN DAERAH SUNGAI OYO, DESA BEJI, KECAMATAN PATUK, KABUPATEN GUNUNGKIDUL, DAERAH ISTIMEWA YOGYAKARTA - Tania, Dina; Kiswiranti, Desi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2021)
The Oyo River, which stretches relatively northwest - southeast in Beji Village, has seven rock facies that make up the Sambipitu Foundation with marl lithology, then the Oyo Formation is deposited on it with claystone lithology, breccia, tuff and sandstones, and the Wonosari Formation with calcirudite lithology and calcarenite based on stratigraphic measurements as thick as 165 meters with dips ranging from 5o-15o. The variation in the composition of the bentonic foraminifera shell wall in the Oyo River rocks reflects environmental changes from normal marine lagoon and carbonate platforms to a continental slope and sea shelf when referring to the triangular plot of Murray (1991) and Brasier (1980) based on the type of shell composition Loeblich and Tappan (1988). The existence of sedimentary structures also shows a transition from a lower fan in the Sambipitu Formation to a suprafan lobes on the mid fan in the Oyo Formation based on the underwater fan model Walker (1978) and ending up as an inner ramp according to Buchette and Wright (1992) by Tania (2019). This is in line with the depositional environment by Tipsword et.al. (1966) and the foraminifera group by Bignot (1982) which shows that the Sambitu Formation is dominated by porcelaneous in the middle bathyal, then the Oyo Formation is dominated by agglutine in the upper bathyal and the Wonosari Formation on the outer-inner neritic is dominated by porcelaneous.middle bathyal, then the Oyo Formation is dominated by agglutine in the upper bathyal and the Wonosari Formation on the outer - inner neritic is dominated by porcelaneous.